Efficacy and safety of copanlisib in relapsed/refractory B-cell non-Hodgkin lymphoma: A meta-analysis of prospective clinical trials - Wang, Jinjin; Zhou, Hui; Mu, Mingchun; Zhao, Ailin; Cai, Zhaolun; Li, Linfeng; Wang, Mengyao; Niu, Ting (Frontiers in Immunology, 2022)
Background Copanlisib is an intravenously administered pan-class I PI3K inhibitor that has been demonstrated to have appreciable effects in the treatment of patients with lymphoma. The purpose of this meta-analysis was to evaluate the efficacy and safety of copanlisib for treating patients with relapsed/refractory (R/R) B-cell non-Hodgkin lymphoma (B-NHL). Methods PubMed, Web of Science, EMBASE, and the Cochrane Central Register of Controlled Trials were searched for relevant studies published prior to July 2022. The efficacy evaluation included complete response rate (CR), partial response rate (PR), rate of stable disease (SDR), overall response rate (ORR), disease control rate (DCR), rate of progressive disease (PDR), median progression-free survival (PFS), and median overall survival (OS). Any grade adverse events (AEs) and grade ≥3 AEs were synthesized to assess its safety. Results Eight studies with a total of 652 patients with R/R B-NHL were identified. The pooled CR, PR, ORR, SDR, DCR, and PDR from all 8 articles were 13%, 40%, 57%, 19%, 86%, and 9%, respectively. The CR and ORR of combination therapy with rituximab were higher than those with copanlisib monotherapy for R/R B-NHL (34% vs. 6%, p<0.01; 89% vs. 42%, p<0.01). For patients with R/R indolent B-NHL, CR and ORR were lower with copanlisib monotherapy than with combination therapy with rituximab (7% vs. 34%, p<0.01; 58% vs. 92%, p<0.01). In R/R B-NHL patients receiving copanlisib monotherapy and combination therapy with rituximab, the risk of any grade AEs was 99% and 96%, respectively, and the risk of grade ≥3 AEs was 84% and 91%, respectively. The common any grade AEs included hyperglycemia (66.75%), hypertension (48.57%), diarrhea (35.06%), nausea (34.98%) and fatigue (30.33%). The common grade ≥3 AEs included hyperglycemia (45.14%), hypertension (35.07%), and neutropenia (14.75%). The comparison of AEs between the copanlisib monotherapy and the combination therapy with rituximab showed that hyperglycemia of any grade (p<0.0001), hypertension of any grade (p=0.0368), fatigue of any grade (p<0.0001), grade ≥3 hypertension (p<0.0001) and grade ≥3 hyperglycemia (p=0.0074) were significantly different between the two groups. Conclusion Our meta-analysis demonstrated that the efficacy of both copanlisib monotherapy and combination therapy with rituximab in patients with R/R B-NHL was satisfactory, while treatment-related AEs were tolerable. Compared with copanlisib monotherapy, combination therapy with rituximab showed superior efficacy for treating R/R B-NHL, and its safety was manageable. Systematic Review Registration https://inplasy.com/inplasy-2022-10-0008/, identifier INPLASY2022100008.